Vehicle front impact safety design using a hybrid methodology. (26th February 2007) - Deb, A.; Chou, C.C.
Computer-aided engineering (CAE), based on techniques like finite element modeling and analysis, can be considered as the backbone for designing complex systems such as automobiles. However, for highly nonlinear problems such as automotive crashworthiness and occupant safety design, a major problem is posed in terms of computational efficiency, modelling efforts, and model quality. For a design engineer, thus, judicious employment of various tools such as statistical regression analysis, lumped parameter modeling, and detailed finite element-based simulation can be the key for achieving an optimised design in a competitive design cycle. The current study highlights a hybrid methodology resulting from the application of these various techniques in an integrated manner for front impact safety design of vehicle platforms. In particular, new regression models are presented and the hybrid approach is demonstrated with an aluminium-intensive vehicle using LS-DYNA for detailed frontal US-NCAP analysis.